Effect Of Polystyrene-Modified Natural Rubber (SNR) On Mechanial Properties Of Waste Natural Rubber Latex/Polystyrene Blend (WNRL/PS). - Orathai, Boondamnoen; Ariffin, Azlan; A. Rashid, Azura; Masahiro, Ohshima; Saowaroj, Chuayjuljit (2010)

(untitled)
Interests on recycling of rubber products are augmenting due to the serious environmental hazard. Furthermore, recycling give economic advantages cheaper materials could be produced.